DadY (PA5303) is required for fitness of Pseudomonas aeruginosa when growth is dependent on alanine catabolism - Ronnie L. Fulton; Diana M. Downs (Microbial Cell, 2022)
Pseudomonas aeruginosa inhabits diverse environmental niches that can have varying nutrient composition. The ubiquity of this organism is facilitated by a metabolic strategy that preferentially utilizes low-energy, non-fermentable organic acids, such as amino acids, rather than the high-energy sugars preferred by many other microbes. The amino acid alanine is among the preferred substrates of P. aeruginosa. The dad locus encodes the constituents of the alanine catabolic pathway of P. aeruginosa. Physiological roles for DadR (AsnC-type transcriptional activator), DadX (alanine racemase), and DadA (D-amino acid dehydrogenase) have been defined in this pathway. An additional protein, PA5303, is encoded in the dad locus in P. aeruginosa. PA5303 is a member of the ubiquitous Rid protein superfamily and is designated DadY based on the data presented herein. Despite its conservation in numerous Pseudomonas species and membership in the Rid superfamily, no physiological function has been assigned to DadY. In the present study, we demonstrate that DadA releases imino-alanine that can be deaminated by DadY in vitro. While DadY was not required for alanine catabolism in monoculture, dadY mutants had a dramatic fitness defect in competition with wild-type P. aeruginosa when alanine served as the sole carbon or nitrogen source. The data presented herein support a model in which DadY facilitates flux through the alanine catabolic pathway by removing the imine intermediate generated by DadA. Functional characterization of DadY contributes to our understanding of the role of the broadly conserved Rid family members.